The effect of video presentation on hotel booking intentions: a conceptual model - Amin, Dawood; Mahomed, Anuar Shah Bali; Ab Aziz, Yuhanis; Hashim, Haslinda; Mohsin Ali, Rana (Publications International, 2019)
The tourism industry has been growing tremendously throughout the world especially during the last two decades. The number of international tourists is forecasted to reach 1.4 billion travelers in 2020. In 2016 only, the hotels worldwide made a revenue of 550 billion U.S. dollars. These figures show the importance of the tourism industry in the general and hotel sector in particular and their significant contribution to the world economy. Consequently, hoteliers are forced to enhance their website design by exploring the factors that affect the booking intention and through understanding the behavior, the needs and the expectations of the travelers since they are in desperate need of solutions to overcome the current challenges and potential risks. The purpose of this study is to develop a conceptual framework to explore the factors that influence the online hotel booking intention and examine the relationship between video presentation and online booking intention utilizing Technology Acceptance Model (TAM) as a theoretical framework.